Image analysis using recurrence quantification plots, surface modeling and fused deposition modeling tools to design 3 dimensional models. Issue 5 (3rd September 2018) - Urbanic, R. Jill
ABSTRACT: Recurrence quantification analysis is a data analysis tool employed to visualise dynamic, non-linear, noisy data. This tool produces graphical displays for systems that have inherently non-predictable behavior. The graphical displays to explore system characteristics are 2D, and may use color coding to represent certain conditions. A method to create 3D results, and dynamic RQ plot visualization via rapid prototyping tool path visualization tools, is presented in this research. The inputs are linear data series created from digital image position and pixel color pairs. This 3D model introduces an additional mode to evaluate recurrence quantification results, and provides a platform for employing Boolean analysis to explore additional insights. GRAPHICAL ABSTRACT: